THEMATIC ORGANIZATION IN ELEVENTH GRADE STUDENTS' EXPOSITION TEXTS - Rahmawati, Erma (2016)
The study aimed to find out how the texts are structured and which theme progression pattern occurs most dominantly in students' exposition text. This study employed a descriptive method embracing the characteristics of a case study approach. The main data were six exposition texts (final draft) written by eleventh grade students divided into three levels according to their achievement. The texts were analyzed by examining the schematic structure and the theme progression using Theme System derived from Systemic Functional Linguistics proposed by Halliday. The findings showed that all students are well informed about the purpose of an exposition text and know how to write the text according to the criteria. In terms of theme progression, the pattern that occurs most dominantly is reiteration pattern. It shows that the students have a clear and strong theme focus. However, the organization of the text is still inadequate for some students. It may results to the failure of completing the purpose of an exposition text. Therefore, some suggestions are recommended.;--- Penelitian ini bertujuan untuk meneliti struktur skematik dan pola theme progression yang paling sering muncul dalam teks eksposisi siswa. Dalam pelaksanaannya penelitian ini menggunakan metode deskripsi dengan mengemban karakter studi kasus. Data utama dalam penelitian ini adalah enam teks eksposisi (draft akhir) yang ditulis oleh siswa kelas sebelas yang kemudian dibagi menjadi tiga level sesuai dengan kemampuan siswa. Teks tersebut dianalisis menggunakan theme system. Dari hasil temuan menunjukkan bahwa semua siswa mengetahui akan tujuan teks eksposisi dan bagaimana menulis teks tersebut sesuai dengan kriteria. Selain itu, theme progression yang paling sering muncul adalah pola reiteration. Hal ini menunjukkan bahwa siswa memiliki fokus yang jelas dan kuat dalam menulis teks. Namun, pemenuhan kriteria dalam hal pengorganisasian teks masih belum mencukupi. Hal ini dapat menyebabkan kegagalan dalam memenuhi tujuan teks eksposisi. Maka dari itu, penulis merekomendasikan beberapa saran.